Evaluation of Indicator Tests for Identification of Segregation in Flexible Pavements - A Case Study (Malaysian Journal of Civil Engineering, 2018)
Segregation of hot mix asphalt (HMA) is a continuing problem in constructionpractice which has caused premature distress in many flexible pavements. Astudy, funded by the Kansas Department of Transportation, was conducted on anewly constructed pavement to evaluate the effectiveness of indicator tests mdetection of segregation.Cores were obtained from segregated and non-segregated areas of the pavementand the unit weights of the pavement were determined using a thin-lift nucleargauge. The change gradation on the 4.75 mm sieve was compared with theindicator tests of asphalt content, i.e., nuclear gauge unit weight, core unit weightand macrotexture.The results of this study indicate that asphalt content is the best indicator test ofsegregation whilst macrotexture is the best non-destructive indicator test ofsegregation.